Pengaruh Gaya Hidup, Media Sosial dan Lingkungan Sosial terhadap Perilaku Konsumsi di Masa Pandemi Menurut Ekonomi Islam:: Studi pada Mahasiswa Prodi Ekonomi Islam Fakultas Ekonomi Dan Bisnis Islam UIN Sumatera Utara Medan - Nurma Hasanah; Tuti Anggraini; Rahmat Daim Harahap (MES Bogor, 2023)
According to Islamic economics, the goal of this research was to establish the influence that a person's lifestyle, social media, and social surroundings have on their purchasing behavior while the epidemic is ongoing. In this research, quantitative methods and associative approaches have been used. For the purpose of data collection, questionnaires have been employed, and both the population and the sample have consisted of 94 individuals. Multiple linear regression was the approach that was utilized to analyze the data. The findings of this research indicate that the Lifestyle Variable (X1) has a significant effect on Consumption Behavior. This is demonstrated by the t count value of 3.422 > t table 1.986 with a significant value of 0.008 0.05. Additionally, the findings of this research indicate that the Social Media Variable (X2) has a significant influence on Consumption Behavior. This consumption behavior is evidenced by the t-count value, which is 4.299 > t table 1.986 with a significant value of 0.007 0.05, the Social Environment Variable (X3) has a significant influence on consumption behavior, this is evidenced by the t-count value, which is 5.919 > t table, and the significance of this influence is shown by the value 0.007 0.05. The variables of Lifestyle, Social Media, and Social Environment all have a simultaneous and substantial impact on Consumption Behavior. The value of 1.986 indicates that this influence is significant, and the significant value is 0.000 0.05. Consumption of 55.8%, as well as the concept of consumption in Islamic Economics for the purpose of fulfilling the many requirements of human existence, meaning that requirements take priority over preferences. When compared to contemporary economics, which places an exclusive emphasis on materialistic pursuits, there is a substantial divergence. The principle in Islam regarding consumption, is governed by five main principles, namely: justice, modesty, morality, cleanliness, and generosity. Keywords: Lifestyle, Social Media, Social Environment, Consumption Behavior